Socio-Economic and Livelihood Assessment of Inland Fishermen in Muda River Basin - Sim, Lay Mei; Chan, Ngai Weng; Tan, Mou Leong; Daud, Norhanida; Ismail, Wan Ruslan; Phang, Wai Leng (European Publisher, 2019)
The Muda River is a shared watercourse between Kedah and Penang state. The inland fishery sector of Malaysia is an important socio-economic sector as it provides a vital source of protein, employment and livelihood for fishers who solely depend on it. However, anthropogenic and environmental issues such as water pollution, eutrophication, depletion of water level, erosion, sedimentation, and overfishing have further compounded the fish environment in Muda river basin. This study was conducted to evaluate the socio-economic and livelihood status of the inland fishermen around Muda river basin. A total of 46 fishermen respondents were selected randomly from the list of fishermen with the Department of Fisheries. The sample survey was carried out in November 2018 and data were analysed using Statistical Package for Social Sciences (SPSS). The data interpretations showed that majority of the fishermen community are literate and the highest level of education in the fishermen community is Form 6 or Diploma. The findings show that primary occupation of the respondents was fishing and some of them are doing odd jobs and working in farmland to create a secondary source of income source. Lack of proper knowledge, research, data, training and much of governmental support was the major constraints of inland fisheries in the study area. It is recommended that the government should closely monitor fisheries in the area in order to prevent overfishing, work with NGOs and at the same time look into the welfare and livelihood of the fishermen.